2022
DOI: 10.3389/fimmu.2022.903796
|View full text |Cite|
|
Sign up to set email alerts
|

CD317-Positive Immune Stromal Cells in Human “Mesenchymal Stem Cell” Populations

Abstract: Heterogeneity of bone marrow mesenchymal stromal cells (MSCs, frequently referred to as “mesenchymal stem cells”) clouds biological understanding and hampers their clinical development. In MSC cultures most commonly used in research and therapy, we have identified an MSC subtype characterized by CD317 expression (CD317pos (29.77 ± 3.00% of the total MSC population), comprising CD317dim (28.10 ± 4.60%) and CD317bright (1.67 ± 0.58%) MSCs) and a constitutive interferon signature linked to human disease. We demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 108 publications
1
20
0
Order By: Relevance
“…In this review, numerous MSC subpopulations identified through marker-based sorting have demonstrated significant Chen et al Journal of Translational Medicine (2024) 22:459 therapeutic efficacy in animal models. These subpopulations mainly exhibit enhanced therapeutic effects through their potent immunosuppressive capabilities, which have been validated across various animal models of inflammation [38,68,74,112,114]. Additionally, some subpopulations possess superior homing and regenerative properties, contributing to tissue repair in the rat model of myocardial infarction and the mouse model of hindlimb ischemia [31,33,124,125].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this review, numerous MSC subpopulations identified through marker-based sorting have demonstrated significant Chen et al Journal of Translational Medicine (2024) 22:459 therapeutic efficacy in animal models. These subpopulations mainly exhibit enhanced therapeutic effects through their potent immunosuppressive capabilities, which have been validated across various animal models of inflammation [38,68,74,112,114]. Additionally, some subpopulations possess superior homing and regenerative properties, contributing to tissue repair in the rat model of myocardial infarction and the mouse model of hindlimb ischemia [31,33,124,125].…”
Section: Discussionmentioning
confidence: 99%
“…Using the hTERT immortalized human bone marrow MSC colonies, it has been demonstrated that the MSCs from the CD317 + colony have increased cell areas and up-regulated mRNA levels of immunosuppressive genes than the CD317 − MSCs in vitro [ 67 ]. Furthermore, CD317 + bone marrow-derived MSCs have better regeneration capabilities than the CD317 − MSCs [ 68 ]. However, fresh CD317 − MSCs isolated from human bone marrow have better immune suppression activities but not CD317 + MSCs [ 68 ].…”
Section: St Generation Of Msc Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Y201 and Y202 BMSCs display considerable variation in morphology, migration, transcriptional profiles and function, highlighting a need for further refinement of stromal identity [24].…”
Section: Introductionmentioning
confidence: 99%
“…Both of these BMSC lines express cell surface proteins described by Dominici, et al [23] well as the commonly reported marker leptin receptor (LEPR). However, Y201 and Y202 BMSCs display considerable variation in morphology, migration, transcriptional profiles and function, highlighting a need for further refinement of stromal identity [24].…”
Section: Introductionmentioning
confidence: 99%